Humble consulting : how to provide real help faster - Schein, Edgar H. (Berrett-Koehler Publishers, Inc., 2016)
Organizations face problems today that are too messy and complicated for consultants to simply play doctor: run a few tests, offer a neat diagnosis of the "problem," and recommend a solution. With the pace of change accelerating and globalization and specialization adding new layers of complexity, there is no time for diagnoses. Canned answers from outsiders have become useless. Well-meaning consultants often end up working on the wrong problem, misunderstanding the client organization's culture, or ignoring the fact that constant change makes today's solutions obsolete tomorrow. In Humble Consulting, Edgar Schein outlines the basics of a new approach. He argues that consultants and coaches have to jettison the old idea of professional distance and work with their clients in a more personal way, emphasizing authentic openness, curiosity, and humility. Schein shows how to create an atmosphere of genuine trust and caring so that clients can share what's really on their minds. Consultants and clients can then jointly discover what needs to be done. Working together from the outset like this speeds things up as it obviates the need for elaborate diagnostic tests and avoids solutions that might look good on paper but don't fit an organization's on-the-ground reality. Schein draws deeply on his own decades of experience, offering over two dozen case studies that illuminate each stage of the humble consulting process. Just as he did with Process Consultation nearly fifty years ago, Schein has once again revolutionized the field, enabling consultants to be more genuinely helpful and vastly more effective